PENERAPAN MODEL ACTIVE LEARNING DAPAT MENINGKATKAN HASIL BELAJAR LOMPAT JAUH PADA MATA PELAJARAN PENDIDIKAN JASMANI DAN OLAHRAGA SISWA KELAS IV SEKOLAH DASAR NEGERI 006 RAMBAH - Baiti Baiti (STKIP Rokania Pasir Pangaraian, 2019)
This class action research generally aims to improve learning outcomes of Physical Education in long jump materials of students class IV through the application of Active Learning models in semester 1 of Primary School 006. The data in this study were collected using tests, student observation sheets, teacher observation sheets, and assessment (performance) rubric of the long jump ability. This type of research is classroom action research. The research procedure consists of planning, implementation, observation and reflection. The results revealed that the results of the preliminary tests showed that the absorptive capacity of the results of the analysis showed that students' learning achievement had increased from cycle I to cycle II, namely pre-cycle (65.41%), cycle I (73.91%), cycle II 79.13%). Based on the research conducted, it can be concluded that the Active Learning model can have a positive effect on the learning outcomes of the long jump in Primary School 006 Rambah of school year 2017/2018, and this learning model can be used as an alternative learning method for Physical Education